Correction: Analysis of Alcohol Industry Submissions against Marketing Regulation - Martino, Florentine Petronella; Miller, Peter Graeme; Coomber, Kerri; Hancock, Linda; Kypri, Kypros (PLOS ONE, 2017)
null